Fontes e épocas de aplicação de fertilizantes orgânicos no amendoim - Silva, Flávio Maria Guterres da (2010)
The aim of this study was to evaluate the behavior of peanut (Arachis hypogaea L.) variety BR-1 under different periods of application of organic sources. The experiment was conducted in a greenhouse without temperature control, at the headquarters of EMBRAPA /CNPA, Campina Grande, from October 2009 to March 2010. The treatments were distributed in 4 x 3 factorial arrangement, consisting of four periods of manure application (0, 15, 30 and 45 days before sowing) and three organic sources (manure cattle, goat and poultry) with four replications in completely randomized design. Peanuts have a significant effect on age assessment in main stem length, leaf area and number of branches, was also significant in interaction between age assessment with organic sources applied to the last variable. Regarding of the peg not reach the ground, number of pods produced and root dry matter were influenced significantly by the organic sources applied, while the number of normal pods and shoot dry matter showed a significant effect for treatments, both in times of application and organic sources. The use of poultry manure as organic source provided higher biomass of peanut. The peanut has benefited from fertilization with poultry manure to produce more normal pods and, consequently, increased production of pods. The peanut production was negatively influenced by the use of poultry manure, goat manure and cattle manure before sowing.